PENGARUH PENGENDALIAN INTERNAL DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN PERILAKU ETIS SEBAGAI VARIABEL MODERATING - Farah Nur Fadhilah; Muhammad Wahyudin Abdullah; Suhartono Suhartono (ISAFIR: Islamic Accounting and Finance Review, 2021)
This study aims to examine the effect of internal control and compliance with accounting rules on the tendency of accounting fraud with ethical behavior as a moderating variable. This research is a quantitative research with a causal approach. The population in this study were managers, assistant managers, staff and finance, internal auditors and supervisors totaling 34 employees. The technique in selecting the sample uses probability sampling, with the sampling method using a saturated sample. The test results in this study indicate that: 1) Internal control has a negative effect on the tendency of accounting fraud, 2) Compliance with accounting rules affects the tendency of accounting fraud, 3) Ethical behavior strengthens the relationship of internal control to the tendency of accounting fraud, 4) Ethical behavior does not strengthen or weakening the relationship of obedience to accounting rules to the tendency of accounting fraud.